2003
DOI: 10.1080/08035250310003857
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress during pregnancy and the risk of infantile colic: a follow-up study

Abstract: The results indicate that general distress during pregnancy influences the risk of infantile colic. Whether or not this relationship is causal requires further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We obtained information on maternal stress from a telephone interview taken around 30 weeks of gestation. We studied two a priori –defined types of stress—emotional stress and life stress—as used in previous studies (Sondergaard et al 2003; Tegethoff et al 2010a, 2010b). The separation of these two types of maternal stress is theoretically based on the well-described stressor specificity of biological responses, which may differentially affect the fetus (Pacak and Palkovits 2001; Richardson et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained information on maternal stress from a telephone interview taken around 30 weeks of gestation. We studied two a priori –defined types of stress—emotional stress and life stress—as used in previous studies (Sondergaard et al 2003; Tegethoff et al 2010a, 2010b). The separation of these two types of maternal stress is theoretically based on the well-described stressor specificity of biological responses, which may differentially affect the fetus (Pacak and Palkovits 2001; Richardson et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained information on maternal stress during pregnancy from a computer-assisted interview taken around 30 weeks gestation. We defined life stress and emotional symptoms as previously described [8], [14]: The applied inventory on emotional symptoms during pregnancy is a modified version of the short version of the Symptom Checklist (SCL)-8d [15] and covers self-reported maternal feelings (e.g. anxiety, nervousness, for detailed description of items, see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…We a priori defined two common forms of maternal stress, self-reported life stress in terms of burdens in major areas of life, and emotional symptoms [8]. The separation of these two major subtypes of maternal stress is based on their possible differential effects on the fetus [9] and the stressor-specificity of biological responses [10], [11], which may differentially affect the placenta via different biological pathways [12].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal depression during early pregnancy has been clearly linked to subsequent infantile colic. 31,32 In one study, there was a threefold increased risk of infantile colic in mothers who reported distress during pregnancy. 32 Interestingly, after adjustment for maternal depressive symptoms, paternal depression has also been associated with colic, as suggested by a prospective population-based study in 4426 2-month-old infants by van den Berg.…”
Section: Etiologymentioning
confidence: 99%